1997
DOI: 10.1111/j.1465-7295.1997.tb02029.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Origins: A Longitudinal Inquiry

Abstract: Ever since Schumpeter identi3ed the "animal spirits" of entrepreneurs as the driving force of markets, researchers have been trying to determine who is an entrepreneur and what factors breed entrepreneurial success. Using data from the National Longitudinal Surveys of Youth, we first determine who pursues self-employment in their youth, and then who succeeds. There is a surprisingly high incidence of self-employment, but very low success rates. Significant correlates of both entry into self-employment and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
5
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 11 publications
8
90
5
10
Order By: Relevance
“…Empirical studies generally support this positive relationship (Gimeno et al, 1997;Bosma et al, 2004;Holmes and Schmitz, 1996;Taylor, 1999;Reynolds, 1993;Lerner et al, 1995;Evans and Leighton, 1989;Santarelli et al 2009;Santarelli and Tran, 2011;Schiller and Crewson, 1997).…”
Section: Human Capital and Entrepreneurial Performancementioning
confidence: 99%
“…Empirical studies generally support this positive relationship (Gimeno et al, 1997;Bosma et al, 2004;Holmes and Schmitz, 1996;Taylor, 1999;Reynolds, 1993;Lerner et al, 1995;Evans and Leighton, 1989;Santarelli et al 2009;Santarelli and Tran, 2011;Schiller and Crewson, 1997).…”
Section: Human Capital and Entrepreneurial Performancementioning
confidence: 99%
“…This concerns their previous position before starting their own business, the entrepreneur's years of prior experience in a similar (growing and attractive) industry (see also Storey, 1994;Glancey et al, 1998), and the information they receive from social family and relatives. The entrepreneur's previous educational attainments and work experience in the long run (learning-by-doing) in a similar type of business (see also Chell et al, 1991;Box et al, 1995 Schiller andCrewson, 1997), coupled with an innovative and positive entrepreneurial attitude (e.g. being a hard worker, acceptance of risk, loyalty, participating in a strong social network) and motivation (e.g.…”
Section: Figure 8: Structural Relations Modelmentioning
confidence: 99%
“…So also, Cooper and Gascon (1992) found that individual variables (personality traits and demographic characteristics) were relatively poor predictors of survival and success let alone of specific organizational behaviour such as innovativeness. In contrast, Mumford and Gustafson's (1988) study suggested that education is important to innovation, while Schiller and Crewson, (1997) stated that education and experience were positively correlated with entrepreneurial performance. The present study is therefore designed to clarify the factors that influence women entrepreneurial innovative behaviour.…”
Section: Literature Reviewmentioning
confidence: 78%